Analysis of Violence in School Based on News Exposed in Mass Media - Al Aziz, Haerul; Dermawan, Mohammad Kemal (Syntax Literate, 2021)
Schools are educational institutions that are expected to be a safe place for all school members, without exception. However, in the last five years, based on KPAI data regarding cases of child complaints, there were 3194 cases of violence in schools that emerged. This study analyzes violence in schools based on news that appears in the mass media, from 2016 to 2020. The data is analyzed using Microsoft Excel using the Pivot Table feature. As a result, there were 112 cases dominated by physical violence as much as 68.75%. The specifications of violence that most often occur in schools are persecutions and beatings as much as 29.46% and 22.32%, respectively. In terms of education level, violence that occurs in senior high school has the highest frequency. In addition, students dominate violence in schools as much as 50% as perpetrators and as victims as much as 85.71%. Systematic prevention efforts are needed in order to reduce various irregularities that occur in schools, especially violence itself